Teknis Penyusunan Rencana Kerja Perpustakaan - Affandi A; Yunidar Purnama Sari; T. Ade Vidyan Magfirah TB (Universitas Teuku Umar, 2021)
Libraries have an important role in improving the quality of Human Resources. One of the successes of an educational institution in providing and running a learning service process can be seen from the library management system provided. This socialization and discussion activity was carried out at the Faculty of Adab and Humanities, UIN Ar Raniry, Banda Aceh City. It aims to improve the ability of library managers to manage libraries in an organized and modern way, able to identify important things in solving various problems that occur in the management and development of school libraries. The technical preparation of library work plans in the industrial era 4.0, using the SWOT Analysis Method so that the advantages and disadvantages can be mapped properly and self-evaluation of library staff and implementing agencies can be recorded properly. The technical activity of preparing a library work plan is expected to make professional librarian staff ready to face library problems that continue to develop.